Thyroid status in patients undergoing maintenance haemodialysis: a South Indian cohort study - S., Bhaskaran; S., Sakthidasan; Shanmugam, Lalitha; C., Suthakaran (International Journal of Advances in Medicine, 2019)
Background: Hypothyroidism is common throughout the world and the prevalence of hypothyroidism is high in India. Ailment of thyroid function has been documented to occur at a higher rate in patients with chronic kidney disease (CKD), including those undergoing dialysis than in general population. Methods: A prospective cross-sectional observational clinical study in real time was carried out to assess the thyroid status in eighty-nine adult patients undergoing a 4 h three times weekly haemodialysis schedule in a rural tertiary referral hospital in South India. The status of the thyroid was monitored via Free T3 Free T4 and Thyroid Stimulating Hormone levels. Results: Subclinical hypothyroidism was common in patients undergoing haemodialysis. Although there was a negative correlation between the levels of thyroid hormones and other variables, it was clinically insignificant. Conclusions: The present study showed that abnormalities in thyroid function are high in patients undergoing haemodialysis and that there were no clinically significant correlation between the levels of thyroid hormones and clinical or biochemical characteristics.